(untitled) (College of Basic Education Research Journal, 2025)
Study aimed to identify efficiency of five-year learning cycle strategy on achievement in discus throwing , as well as knowing differences between two research groups (experimental and control) between post-tests in cognitive , skill and achievement of discus throwing. Researcher assumed that there was a significant difference in results of two research groups (experimental and control) between pre- and post-tests in discus throwing , in addition to a significant difference in results of two research groups (experimental and control) between post tests of achievement in discus throwing Research community was determined in a deliberate manner, represented by students of second stage in Department of Physical Education and Sports Sciences - College of Basic Education / University of Mosul for the academic year (2023-2024). Total number of students in this stage (81) male and female students distributed over three classes . First class contained (26) students, second (25) , and third (30) male and female students, divided into (20) male and (10) female students. Researcher used statistical package (25 - SPSS) to obtain results . Researchers concluded. Efficiency of five-year learning cycle strategy and current method used in developing skill attainment and achievement for two research groups (experimental and control). In discus throwing . Experimental group that applied five-year learning cycle strategy outperformed control group in cognitive achievement of discus throwing. Reaching these results, researcher made several recommendations, the most important of which was: Necessity of adopting and applying five-year learning cycle strategy in the process of teaching discus throwing , in order to demonstrate its effectiveness in gaining cognitive and skill achievement and achieving this event, as well as adopting and applying five-year learning cycle strategy